LoRaWAN Network Planning for ODP Door Monitoring in Banyumas Districts - I Ketut Agung Enriko; Fikri Nizar Gustiyana; Gilang Hijrian Fahreja; Gede Candrayana Giri (JAICT, 2023)
This study aims to design a LoRaWAN network on the coverage side to find out how many gateways are needed and to design an IoT-based monitoring system at ODC doors to minimize damage due to vandalism or forced opening. The method used is a simulation using Atoll software version 3.40 and several stages of calculations to predict signal strength and quality in the Banyumas Regency area. This study uses a frequency of 920 MHz with a bandwidth of 125 kHz and a Spreading factor of 1 to 12. The results obtained are a comparison of the number of gateways, signal strength and signal quality based on variations in the spreading factor. SF 7 produces 104 gateways with a signal strength of -71.88 dBm and a signal quality of 9.43 dBm. spreading factor. SF 12 produces 48 gateways with a signal strength of -79.8 dBm and a signal quality of 10.78 dBm. The larger the SF used will improve signal quality but reduce signal strength and also fewer gateways.